Biotransformation of soluble starch to cyclodextrin using immobilized recombinant escherichia coli on hollow fiber membrane - Nur Nadia, Mohd Zakaria (2023)
The growing interest of industries toward β-cyclodextrin (β-CD) is undeniably due to its unique structure that capable of forming inclusion agent. β-CD has been widely used in numerous industries such as in pharmaceutical, cosmetic and biotechnology. β-CD is form through the enzymatic reaction between cyclodextrin glucanotransferase (CGTase) and starch. The CGTase can be found naturally in Bacillus sp. However, Bacillus sp. produce low amount of CGTase. Thus, genetically modified E. coli can be used to solve the problem by producing high amount of CGTase. The drawbacks of CGTase production when using E. coli as a host is the occurrence of cell lysis. Hence, cell immobilization is an alternative way to reduce the cell lysis with high CGTase production. Adsorption is well known technique in cell immobilization. The advantage of adsorption technique is simple, direct contact between nutrients and matrix, and enhancing the cell stability with high yield of cell immobilization. Besides, kinetic study is also performed to understand the mechanism of adsorption reaction. The objectives of this study are to optimize the immobilization yield by manipulating the process parameters of the recombinant E. coli cells on the hollow fiber membrane via adsorption technique and to evaluate the performance of immobilized CGTase on the production of CD. The recombinant E. coli was immobilized on the hollow fiber membrane. The effect of contact time, temperature, agitation rate, pH and type of medium on the cell immobilization yield (cell concentration) was investigated by using one-factor-at-one-time (OFAT) method. The cell concentration by the immobilized cells showed 150 mg/ml under the conditions of 24 hr of contact time, 200 rpm and pH 7 at 30 °C by using Terrific broth. The significant of process parameters (temperature and contact time) on the immobilization yield was further optimized by using response surface methodology (RSM). Under the optimized conditions (20 hr of contact time and 35°C), ±227 mg/ml of cell concentration was recorded. The kinetic study of the adsorption of cell onto the hollow fiber membrane was also performed. Based on the correlation coefficient (R2), the best-fitted model is the Pseudo second-order kinetics model (R2 = 0.9515). Besides, the model was also fitted to Langmuir isotherm with the R2 of 0.989. The effect of reaction parameters such as substrate concentration, pH and agitation rate on production of β-CD by the immobilized cells was determined. The result showed that at 6% of substrate concentration, pH 9 and 200 rpm of agitation rate, the highest CD production of ±7.8 mg/ml was produced. Then, at the optimized reaction conditions (200 rpm, pH 8.5 and 5.5% of substrate concentration), the highest CD production (±11.6 mg/ml) was recorded. For the reaction kinetic study, it showed that the Vmax of both immobilized cells (±2.18 mg/ml.hr) and free cells (±2.25 mg/ml.hr) was almost similar. The Km value for the immobilized cells (±5.14 mg/ml) was almost the same as the free cell (±5.42 mg/ml). The immobilized cells also could retain 24.4% from its initial activity even after 6 successful cycles. Thus, these findings showed that the immobilized recombinant E. coli on the hollow fiber membrane is a promising technique to produce high concentration of β-CD.